Factor V Leiden and Factor V R2 Allele: High-throughput Analysis and Association with Venous Thromboembolism - Benson, Jane M.; Ellingsen, Dorothy; El-Jamil, Muhydine; Jenkins, Meredith; Miller, Connie H.; Dilley, Anne; Evatt, Bruce L.; Hooper, Craig W. (Thrombosis and Haemostasis, 2001)
Thrombophilia is a multigenic disease in which the combination of genetic polymorphisms increases the risk of deep vein thrombosis (DVT). The rapid identification of these genetic combinations requires high-throughput analysis of single nucleotide polymorphisms (SNPs). The TaqMan® fluorogenic 5’→3’ nuclease assay (PE/Applied Bio-systems, Foster City, CA) with custom-designed primers, probes and controls has provided a highly efficient platform for high throughput. This assay was used to rapidly detect two SNPs, FV Leiden (G1691A) and FV A4070G (R2 allele), in a study of 6295 subjects. With one thermal cycler, we completed sample set-up, PCR and analysis on 84 samples in 3 h with an additional 12 wells containing 4 “no template controls” (NTC), 4 “allele-1 controls”, and 4 “allele-2 controls” in a 96-well plate. When additional thermal cyclers were used and more assays were set up while the initial sets of reactions were in the PCR machines, the output could correspondingly be increased. The TaqMan® assay was extremely accurate, avoided contamination by using uracil-N-glycolase (UNG) in a single, closed tube, and offered the possibility for additional automation with robotic equipment to implement the PCR. This TaqMan® assay facilitates high throughput to screen large populations quickly and economically while utilizing a simple protocol that requires minimal expenditure of personnel time. Our results demonstrated a prevalence of the R2 allele of 11.9% in U.S. Caucasians, 5.6% in African-Americans, 13.4% in Asian or Pacific Islanders and 11.3% in Hispanics. No association between venous thromboembolism and the R2 allele was noted, and furthermore no interaction with FV Leiden was observed.
Keywords: Factor V Leiden; R2 allele; single nucleotide polymorphisms (SNPs); TaqMan®; venous thrombosis